A reconfigurable high ultimate rejection inductorless band‐pass filter by the use of N‐path passive mixers. (2nd November 2020) - Hazrati, Amin; Jalali, Ali; Meghdadi, Masoud
Summary: In this paper, a band‐pass filter with a tunable bandwidth and the center frequency is introduced, which employs N‐path and N × M‐path passive mixer structures, for multiband multistandard wireless receivers. The center frequency of the proposed filter is tunable from 0.1 to 1 GHz, while its bandwidth is also adjustable from 6% to 34% of the center frequency at 100 MHz. The passband ripple is reduced by applying a Miller compensation technique, resulting in a worst‐case ripple of only 1.6 dB over the entire tuning range. An additional eight‐path filter is also utilized at the input of the circuit, which highly improves the out‐of‐band rejection of the filter as well as its out‐of‐band linearity. The noise figure and the input return loss are, respectively, better than 5 and 10 dB, and depending on the desired center frequency, the total power consumption of the proposed filter varies from 41 to 70 mW. Abstract : This paper presents a method by which the bandwidth of an N‐path bandpass filter is tuned at different center frequencies. Furthermore, the center frequency of the filter is adjustable from 100 MHz to 1 GHz that has high out‐of‐band rejection by the use of filtering at input that relaxes the need for external circuit for providing input impedance matching. Moreover, Miller compensation technique is utilized to improve the passband ripple at different center frequencies and bandwidths.